2023
DOI: 10.1021/acsapm.3c01199
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Antioxidant and UV-Shielding Composite Hydrogel Using Mussel-Inspired Cellulose Nanocrystals, Polydopamine, and Poly(vinyl alcohol) for Application in Sunscreens

Abstract: Sunscreens can help protect the skin from solar ultraviolet (UV) radiation, which is harmful to human health. However, traditional sunscreens can penetrate the skin, raising concerns about their safety. Therefore, fabrication of a sunscreen with biocompatible, UV-shielding, and antioxidant properties is pertinent. Herein, a simple method involving the self-polymerization of dopamine to polydopamine (PDA) was proposed for the surface modification of poly(vinyl alcohol) (PVA) and cellulose nanocrystals (CNCs) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Both of the results indicated that the cell viability is higher than 70%. 40 , 41 Therefore, the biocompatibility tests evidenced that the prepared PVP/CMC hydrogel is nontoxic and biocompatible. It is understandable that both the biocompatible CMC and PVP lead to biocompatible hydrogels.…”
Section: Resultsmentioning
confidence: 97%
“…Both of the results indicated that the cell viability is higher than 70%. 40 , 41 Therefore, the biocompatibility tests evidenced that the prepared PVP/CMC hydrogel is nontoxic and biocompatible. It is understandable that both the biocompatible CMC and PVP lead to biocompatible hydrogels.…”
Section: Resultsmentioning
confidence: 97%
“…In nature, different marine organisms, including mussels, sandcastle worms, and barnacles, , direct a strong wet adhesion mechanism via the elegant combination of catechol chemistry, polyelectrolyte complexes, and supramolecular architectures. This is due to the excellent wet adhesion tenacity that can be mimicked or competed with by the use of 3, 4-dihydroxy- l -phenylalanine (DOPA) groups. , The catechol acts as a crucial functional group on various substrates through catechol chemistry, including hydrogen bonding, π–π interactions, metal coordination, Schiff base reaction or Michael addition, cation–π interactions, hydrophobic interactions, boronate–catechol complexation, and covalent bonds. Based on their understanding of adhesion mechanisms, researchers have also gradually developed a variety of adhesive materials for potential applications, such as bioelectronics and biomedicines. …”
Section: Introductionmentioning
confidence: 99%
“…Based on their understanding of adhesion mechanisms, researchers have also gradually developed a variety of adhesive materials for potential applications, such as bioelectronics 23 and biomedicines. 24 28 …”
Section: Introductionmentioning
confidence: 99%
“…Excessive ultraviolet (UV) radiation could damage our skin in daily life. Prolonged UV irradiation induces the generation of reactive oxygen species (ROS), leading to epidermis inflammation, keratin deposition, and premature aging of the skin, etc. Moreover, UV is harmful to DNA by creating cyclobutene pyrimidine dimers (CPDs) during its replication, resulting in skin cancer. , Various sunscreens have been developed for resisting UV. Inorganic sunscreens, including titanium dioxide (TiO 2 ) and zinc oxide (ZnO), as well as organic sunscreens, such as octyl methoxy cinnamate (OMC) and avobenzone, are strong UV absorbing agents. , However, the high UV-absorbing capacity of these sunscreens is often accompanied by the generation of free radicals. During the photoprotection, inorganic sunscreens yield additional ROS due to their intrinsic photocatalytic activities while organic sunscreens photodegrad into lethal free radicals. Besides, these sunscreens can also penetrate the skin because of their nanosize, eventually triggering inflammations in the tissues or even influencing the circulatory system. ,, Hence, there is a great demand to develop sunscreens with high UV-resistance efficiency as well as credible biosafety.…”
Section: Introductionmentioning
confidence: 99%